English linguistics : essentials - Kortmann, Bernd, 1960- (J.B. Metzler, 2020)
This is the completely revised, updated and enlarged 2nd edition of a classic textbook used in many English and linguistics departments in Germany for more than 20 years. It serves both as an introduction for beginners and as a companion for more advanced undergraduate and graduate students, familiarizing its readers with the major and distinctive properties of English (Standard English as well major national, regional and social varieties), including an in-depth structural comparison with German. Written in an accessible style and with many reader-friendly features (including checklists with key terms and concepts, basic and advanced exercises with solutions), the book offers a state-of-the-art-survey of the core terminology and issues of the central branches of linguistics, including an account of the major current research traditions and methodologies.